2014
DOI: 10.1002/hed.23664
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of nelfinavir as monotherapy in refractory adenoid cystic carcinoma: Results of a phase II clinical trial

Abstract: Background Adenoid cystic carcinoma (ACCs) are malignant salivary gland tumors noteworthy for high rates of late failure with limited salvage therapy options. We have previously shown increased Akt signaling is common in ACC and the HIV protease inhibitor nelfinavir (NFV) inhibits in vitro tumor growth by suppressing Akt signaling. This phase II trial was conducted to determine progression free survival in response to NFV in patients with recurrent/end stage ACC who have failed standard therapies. Methods El… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…Thirty‐six % of subjects had stable disease for >6 months . In another study, no efficacy was observed in 15 patients with adenoid cystic carcinomas . The median progression‐free survival was 5.5 months and no patient achieved a partial or complete response.…”
Section: Clinical Trialsmentioning
confidence: 96%
“…Thirty‐six % of subjects had stable disease for >6 months . In another study, no efficacy was observed in 15 patients with adenoid cystic carcinomas . The median progression‐free survival was 5.5 months and no patient achieved a partial or complete response.…”
Section: Clinical Trialsmentioning
confidence: 96%
“…Nelfinavir, an antiretroviral drug approved for use in HIV treatment, is thought to exhibit inhibition of the Akt signaling pathway and has shown promise as cancer monotherapy in preclinical studies. 116 Hoover et al 116 conducted a phase II clinical trial with nelfinavir in patients with advanced AdCC but no objective responses were observed. Table 2 summarizes studies of targeted therapy in AdCC.…”
Section: Adenoid Cystic Carcinomamentioning
confidence: 99%
“…No meaningful improvement in clinical outcomes was reported among patients with recurrent adenoid cystic carcinomas and nelfinavir (PI) monotherapy in a phase II clinical trial. 191 The use of efavirenz (NNRTI) also did not improve the nonprogression rate of castration-resistant prostate cancer in a phase II clinical trial. 192 A phase II clinical trial of ritonavir/lopinavir (PIs) combination in patients with progressive or recurrent high-grade gliomas did not reveal a potent clinical activity either.…”
Section: Antiretroviral Drugs and Cancer Treatment In Hiv-negative Pamentioning
confidence: 99%